Impact of chemical and organic fertilizer on the yield and nutritional composition of bambara groundnut (Vigna subterranea L. Verdc.) (Bangladesh Journal of Botany, 2019)
A pot experiment was conducted to find out the effects of chemical and organic fertilizer on the yield and nutritional composition of bambara groundnut (Vigna subterranea). The size of the pot was 65.94 cm2. Different rates of compost, biofertilizer, gypsum was used along with the combination of different doses of nitrogen and phosphorus fertilizer. N and P fertilizers were found to play dominating role to increase yield and nutritional composition of the plant. Number of pod (41.75), 100-seed weight (34.25 g), protein (22.15%), Ca (803.25 mg/ka) increased with the application of N and P 30 and 60 kg/ha, respectively which was better than all other treatments. The application of N30 + P60 kg/ha increased yield and nutritional composition of bambara groundnut.